From Single Hydrogen Bonds to Extended Hydrogen‐Bond Wires: Low‐Dimensional Model Systems for Vibrational Spectroscopy of Associated Liquids. Issue 37 (10th July 2013) - Olschewski, Martin; Knop, Stephan; Lindner, Jörg; Vöhringer, Peter
Abstract It is fair to say that if we ever wish to understand the anomalous properties of water, we need to study hydrogen bonds. Such a statement is based on statistical mechanics, which tells us how to calculate the structure and the thermodynamic properties of fluids and dense liquids from the forces between the particles. However, in the case of complex associated liquids, such calculations present a formidable—if not even insurmountable—challenge, which largely reflects our still‐limited understanding of the hydrogen‐bonding phenomenon itself. More experimental research on hydrogen‐bonded systems is required to develop a comprehensive, satisfactory theory for associated liquids. This Review gives an introduction to the latest experimental technique currently being used to study the ultrafast structural dynamics of hydrogen bonds, namely two‐dimensional infrared spectroscopy, and its applications to hydrogen‐bonded systems of systematically increasing complexity, starting from the single hydrogen bond of a diol to low‐dimensional extended networks of stereoselectively synthesized polyalcohols.